Caracterización espacial de las propiedades hidrofísicas del suelo en la microcuenca "León Huayco" del Parque Universitario de Educación Ambiental y Recreacional Francisco Vivar Castro - Morocho Suquilanda, Jenny Rosa (2024)
The hydro physical characteristics of soil are defined through the interaction between its attributes, which are key indicators of its physical quality. This study focuses on the characterization of the hydro physical properties of soil in the "León Huayco" micro basin, located in the Francisco Vivar Castro University Park for Environmental and Recreational Education. To this end, eight systematic sampling points were established, considering slopes less than and greater than 30%, with two test pits for each type of vegetation cover (native forest, forest plantation, Andean scrubland and anthropic moorland). In order to describe the profiles, the FAO methodology (2009) was applied and the USDA Soil Taxonomy classification (2014) was used to designate the horizons. The saturated hydraulic conductivity (Ks) is calculated by the constant head permeameter method, the field capacity (FC) at pF 2.54 and permanent wilting point (PMP) at pF 4.2 were calculated using the "Richards Membrane" technique. The micro basin has an area of 0.44 km2, a perimeter of 3.35 km, the average elevation is 2.353 m.a.s.l. and its average slope is 61%. A predominance of loamy textures will be observed, with variations to clayey loam and sandy loam at different depths. The Ks values range go from 0.29 and 8.46 m/day at different slopes which indicates a moderate water carrying capacity. The pH from 3.6 to 5.2 is considered extremely acidic, the organic matter (OM) content varies from 4.72 % to 16.82 % in the first 20 cm of soil. The CC values range between 23 % and 48 % at 1/3 atm, while the PMP at 15 atm is between 8 % and 14 %. The study is essential to understand the water behavior of the micro-basin and plan sustainable management strategies.